(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the fact that peoples have their own principles and methods of translating folklore samples, reflecting their national lifestyle, religious views, customs and traditions, and their own linguistic laws. It is important to prove this in order to identify and solve the problems of artistic translation of folklore works, as well as to determine their scientific and theoretical foundations.